Neurostimulation Combined With Cognitive Intervention in Alzheimer’s Disease (NeuroAD): Study Protocol of Double-Blind, Randomized, Factorial Clinical Trial - Andrade, Suellen Marinho; de Oliveira, Eliane Araújo; Alves, Nelson Torro; dos Santos, Ana Cristina Gomes; de Mendonça, Camila Teresa Ponce Leon; Sampaio, Danielle Dorand Amorim; da Silva, Edyllaine Elidy Querino Cavalcante; da Fonsêca, Égina Karoline Gonçalves; de Almeida Rodrigues, Evelyn Thais; de Lima, Gabriela Nayara Siqueira; Carvalho, Jamerson; da Silva, Jessyca Alves Silvestre; et al. (Frontiers in Aging Neuroscience, 2018)
Despite advances in the treatment of Alzheimer’s disease, there is currently no prospect of a cure, and evidence shows that multifactorial interventions can benefit patients. A promising therapeutic alternative is the application of transcranial direct current stimulation (tDCS) simultaneously with cognitive intervention. The combination of these non-pharmacological techniques is apparently a safe and accessible approach. This study protocol aims to compare the efficacy of tDCS and cognitive intervention in a double-blind, randomized, and factorial clinical trial. One hundred participants diagnosed with mild-stage Alzheimer’s disease will be randomized to receive tDCS and cognitive intervention, tDCS, cognitive intervention, or placebo. The treatment will last eight weeks, with a 12-month follow-up. The primary outcome is the improvement of global cognitive functions, evaluated by the Alzheimer Disease Assessment Scale, cognitive subscale (ADAS-Cog). The secondary outcomes include measures of functional, affective, and behavioral components, as well as a neurophysiological marker (brain-derived neurotrophic factor). This study will enable us to assess, in the short and long term, whether tDCS is more effective than the placebo and to examine the effects of combined therapy (tDCS and cognitive intervention) and isolated treatments (tDCS vs. cognitive intervention) on patients with Alzheimer’s disease.